PENERAPAN BERMAIN KERAREL UNTUK MENINGKATKAN HASIL BELAJAR SENAM KESEIMBANGAN PADA SISWA KELAS II SDN LEREP 05 KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the effort to develop students' skills aimed at producing improvedlearning outcomes gymnastics material balance with bermaian kerarel of class II Elementary School District 05Lerep West Unggaran Semarang regency. The research method used was a qualitative and quantitativeassessment.Data collection techniques using the test observation form of a written test on each cycle and aktvitasobservation sheets for teachers and students. The experiment was conducted in SD N Lerep 05 with grade IIsubjects research, which has 21 students, consisting of 11 male students and 10 female students and teachers.Sources of data obtained from the performance and outcomes of student learning, teacher performance in themanagement of learning, and documents obtained from the findings, the record during the course of the studyconducted in two phases: the first cycle, and II.From the available data it can be concluded that the results of student activity increased in each cycle, the firstcycle was 66.7% with 14 students completed, 90.5% in the second cycle with 19 students completed. In cycle 1mastery of cognitive achievement (61.9%), psychomotor (66.7%), affective (71.4%). In cycle 2 cognitive masteryattainment (90.5%), psychomotor (85.7%), affective (90.5%) with a very good category.